Changes in cytogenetics and molecular genetics in acute myeloid leukemia from childhood to adult age groups - Creutzig, Ursula; Zimmermann, Martin; Reinhardt, Dirk; Rasche, Mareike; von Neuhoff, Christine; Alpermann, Tamara; Dworzak, Michael; Perglerová, Karolína; Zemanova, Zuzana; Tchinda, Joelle; Bradtke, Jutta; Thiede, Christian; et al. (Cancer, 2016)
BACKGROUND: To obtain better insight into the biology of acute myeloid leukemia (AML) in various age groups, this study focused on the genetic changes occurring during a lifetime. METHODS: This study analyzed the relation between age and genetics from birth to 100 years in 5564 patients with de novo AML diagnosed from 1998 to 2012 (1192 patients from nationwide pediatric studies [AML Berlin-Frankfurt-Münster studies 98 and 2004] and 4372 adults registered with the Munich Leukemia Laboratory). RESULTS: The frequencies of cytogenetic subgroups were age-dependent. Favorable subtypes (t(8;21), inv(16)/t(16;16), and t(15;17)) decreased in general from the pediatric age group (2 to < 18 years; 33%) to the oldest groups (<5% for > 70 years; P < .0001). Unfavorable cytogenetics (-7/del(7), -5/del(5q) or 5p, inv(3)/t(3;3), t(6;9), complex karyotype, 12p, 17p, and 11q23/mixed-lineage leukemia aberrations, excluding t(9;11)) were frequent (42%) in infants (<2 years), had a low frequency in children and young adults (<22%), and increased in frequency up to 36% in patients older than 85 years (P = .01). This was even more significant for complex karyotypes (P ≤ .0001), which also showed a strong increase in the absolute age-specific incidence with age. Interestingly, the frequency of 11q23 abnormalities decreased from infants to older patients. The proportion of clinically relevant molecular aberrations of CCAAT/enhancer binding protein α, nucleophosmin (NPM1), and NPM1/fms-related tyrosine kinase 3-internal tandem duplication increased with age. CONCLUSIONS: Altogether, with the exclusion of infants, a significant decrease in the proportion of favorable cytogenetic subtypes and an increase in unfavorable cytogenetics were observed with increasing age. These findings indicate different mechanisms for the pathogenesis of AML; these different mechanisms also suggest directions for etiological research and contribute to the more unfavorable prognosis with increasing age. Cancer 2016;122:3821-3830. © 2016 American Cancer Society.
Keywords: senioři; Nucleophosmin; senioři nad 80 let; Molecular Biology; Male; age groups; kojenec; Prognosis; mladiství; Middle Aged; karyotypizace; mužské pohlaví; molecular genetics; Infant; Leukemia, Myeloid, Acute; Adult; mladý dospělý; Karyotyping; cytogenetické vyšetření; dítě; Child; Aged, 80 and over; Child, Preschool; Infant, Newborn; Young Adult; ženské pohlaví; novorozenec; prognóza; Humans; předškolní dítě; Cytogenetics; molekulární biologie; Chromosome Aberrations; akutní myeloidní leukemie; nukleofosmin; lidé středního věku; chromozomální aberace; acute myeloid leukemia; adults; cytogenetics; dospělí; cytogenetika; Female; Aged; Adolescent; lidé; Cytogenetic Analysis; pediatric